2009
DOI: 10.1055/s-0029-1224188
|View full text |Cite
|
Sign up to set email alerts
|

Übelkeit und Erbrechen als evolutionäre Mechanismen der vielschichtigen Anpassungsreaktion an die Schwangerschaft

Abstract: Our new and previously existing data support the idea that NVP has been selected for by evolution, as a functional adaptation to vulnerable early pregnancy, which benefits mother and child. This assumption is supported by the correlation of NVP with a better foetal prognosis, the cross-culturally high prevalence and a favorable relation of low biological costs versus high effects. The benefit of NVP could be realised by nutritional change, increased social support, more passive and careful behaviour, earlier r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“… 8 It has also been suggested that, in evolutionary terms, NVP could have a protective effect in early pregnancy, realized by nutritional change, increased social support, more passive and careful behavior, earlier recognition of pregnancy and a positive influence on fetal development. 9 It may be no coincidence, therefore, that NVP is associated with fewer fetal deaths and higher birth weight. 10 , 11 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 8 It has also been suggested that, in evolutionary terms, NVP could have a protective effect in early pregnancy, realized by nutritional change, increased social support, more passive and careful behavior, earlier recognition of pregnancy and a positive influence on fetal development. 9 It may be no coincidence, therefore, that NVP is associated with fewer fetal deaths and higher birth weight. 10 , 11 …”
Section: Introductionmentioning
confidence: 99%
“…NVP could have a protective effect in early pregnancy, realized by nutritional change, increased social support, more passive and careful behavior, earlier recognition of pregnancy and a positive influence on fetal development. 9 …”
Section: Introductionmentioning
confidence: 99%